Self-sufficiency policy and irrigated rice productivity in the Senegal River Valley - Diagne, M.; Demont, M.; Seck, P.A.; Diaw, A. (Springer, 2013)
Senegal's high dependence on rice imports exposes the country to international market shocks with concomitant serious risks for food security. Since 2011 and triggered by high international prices, several initiatives to upgrade the rice value chain have emerged in the private sector. However, the major constraint private investors are currently facing is the insufficient supply of Senegal River Valley (SRV) paddy rice, implying that investment in productivity is becoming vital for the continuation of their operations, which are currently running below their optimum. The Senegalese government is investing heavily in the national rice sector, with the ambitious objective of achieving self-sufficiency in the year 2015. However, the program focuses primarily on extension of the area grown rather than increased productivity. We provide econometric support for policy making by assessing the determinants of productivity and technical efficiency in irrigated rice production systems through a five-year panel dataset of small-scale irrigated rice farms in the SRV. We found that due to the exacerbation of biological and institutional constraints in the SRV, rice growers had difficulties in maintaining productivity of their land. These constraints prevented them from further intensification, jeopardizing the national objective of self-sufficiency. Farmers exhibited modest technical efficiency levels, suggesting that, in addition to the proposed intensification strategies, substantial efforts in extension services will be required in order to achieve the goal of self-sufficiency. Improved weed and bird control as well as technological, organizational and institutional improvements were identified as key factors for boosting productivity and technical efficiency and, hence, these are target areas needing attention by Senegalese farmers and policy makers in their quest for increased food security